Analysis of Patient Nutrition Service Management Viewed from the Input, Process and Output Aspects in the Nutrition Installation of the Khidmat Sehat Afiyat Regional General Hospital, Depok City in 2023 - Nurmadinisia, Rahmi (Journal of Religion and Public Health, 2024)
Abstract in EnglishImplementation of nutritional management in hospitals is an important component in nutritional installations which aim to provide food for patients, starting from menu planning to food distribution to achieve optimal nutritional status and maximum recovery for patients. Hospital nutrition services can be carried out well if they are supported by good and efficient nutrition installation management. The aim of the research is to determine and analyze the description of the implementation of nutritional management in inpatients at Khidmat Sehat Afiat Regional Hospital, Depok City in 2023. This research uses analytical qualitative methods with data collection techniques through in-depth interviews using recording equipment, observation sheets, and document review at nutrition installations. The main informants were nutrition installation officers and key informants, heads of nutrition installations and inpatients. The research results show that the implementation of nutrition management starts from the input stage, namely human resources with the requirement of a nutritionist with a minimum diploma education. All officers comply with the SOP by paying attention to hygiene, sanitation and complete use of Personal Protective Equipment.. Budget planning is carried out once a year, originating from the Depok City Government's APBD funds. Menu planning uses an 11 day menu cycle. Orders and purchases are made every 2 days for wet food ingredients and once every 3-4 days for dry food ingredients. Food storage uses the FIFO/FEFO method. Food processing is carried out by looking at the menu cycle based on the recipe. Distribution uses a centralized method with good and timely service. The output is that most patients like the appearance, cleanliness, aroma and taste of the food and are satisfied with the nutritional installation services. The implementation of management in terms of input, process and output at RSUD has largely gone well.